The Influence of Fiber Orientation and Treatment Variation of Natural Fiber Reinforced Composites on Tensile Strength and Toughness - Fandy Prihatna Suhada; Afira Ainur Rosidah; Vuri Ayu Setyowati; Suheni Suheni (Journal of Applied Sciences, Management and Engineering Technology, 2023)
Composites using natural fibers are being widely developed and researched, this is because natural fibers are easy to find and abundant. In this study, the natural fibers used were bamboo fiber and banana stems. Banana fiber has good mechanical properties and is easy to find, while bamboo fiber is easy to find and has a low density. In this study, the aim was to determine the effect of fiber orientation and treatment on the tensile strength and toughness of natural fiber reinforced composites using a polyester matrix. The variation of the fiber orientation used is 30o and 90o, and the fiber treatment used is alkali and bleaching treatment. Based on the research results, the 90o angle with fiber bleaching treatment has the highest tensile strength value, which is equal to 37.33 MPa with a modulus of elasticity of 5 GPa. As for toughness through impact testing, the highest value is 2.74 x 10-2 J/mm2 at an angle of 90o with bleaching treatment.